“Deterioration” and “aging” can modify or breakdown the phytochemical and biochemical characteristics of green cumin (Cuminum cyminum L.), although their effects differ - Hassan Feizi; Mohammad Shahin Daneshmandi; Ali Shayanfar; Anahita Pahlavan (Journal of Agriculture and Food Research, 2024)
Deterioration of medicinal plant and herb's spices seeds has two important aspects; its impact on viability and its influence on food and medicine feedstock. So, in this study was investigated of phytochemical and biochemical composition of green cumin (Cuminum cyminum L.) were evaluated under natural seed storage (NSS) for one and two years and accelerated seed aging process (ASA) for 24, 48, 72 and 96h. Oil percent declined by prolonging ageing duration. The highest amount was measured in control (21.60 %) and the lowest amounts in 2Y NSS (17.83 %) and 96h ASA (15.83 %). There was no significant difference among all treatments in unsaturated fatty acids (USFA) terms, yet percent of saturated fatty acids (SFA) rose by severe ageing condition. Among fatty acids, NSS had a strong correlation with oleic acid (C18:1) (R2 = 0.99 %), while ASA was correlation with stearic acid (C18:0) (R2 = 84 %). Total phenolic content, and under severe ageing were found in cumin. In the oil and essential oil (EO), DPPH showed an ascending trend in NSS treatments and a descending trend in ASA treatments. Additionally, the maximum IC50 was observed in the oil treatment, being approximately 8.6 times higher than that of the EO. 85 %–90 % of the EO compounds present in all treatments consisted of Myrcene, p-Cymene, Cumin aldehyde, and γ-Terpinene-7-al. NSS led to a significant increase in Cumin aldehyde (R2 = 0.99), indicating that enhancing the aroma of green cumin is subject to a period of cumin fruit storage. Finally, it is concluded that ASA can simulate NSS induced changes in oil content, EO components and antioxidant capacity.